1199. Implementation of a Nasal Antiseptic Decolonization Program Reduces the Occurrence of Healthcare-Associated Infections in the Adult Intensive Care Unit Setting. (15th December 2022) - Kreiling, Stephanie; Watson, Rachel; Perez, Gabriela; Carr, Adrienne; Wolfe, Rachel
Abstract: Background: Universal decolonization programs effectively reduce methicillin-resistant Staphylococcus aureus (MRSA) infections, bloodstream infections, and healthcare costs. However, universal decolonization programs that utilize mupirocin may promote antimicrobial resistance. Non-antibiotic interventions, such as nasal antiseptic decolonization, can contribute to the prevention of healthcare-associated infections (HAIs). A large hospital system sought to evaluate the impact of a universal nasal antiseptic program on HAIs in the adult intensive care unit (ICU) setting. Methods: A nasal antisepsis decolonization quality improvement project (QIP) was implemented to reduce ICU HAIs by applying a 62% nasal antiseptic swab with emollients bilaterally to the nares every 12 hours for all adult ICU patients. The program was piloted across nine ICUs at three large hospitals from November 2021 to January 2022 and captured data from 12, 404 patient days and 4, 058 treatment days. Central line-associated blood stream infection (CLABSI), catheter-associated urinary tract infection (CAUTI), and MRSA bacteremia rates were compared a) between treated and non-treated patients during the QIP period and b) to rates during a three-month period prior to the QIP. Results: The results of the pilot program indicated that patients who received treatment with the 62% nasal swab developed fewer HAIs than patients who did not receive the treatment. Two HAIs occurred in the treatment group (two CAUTIs) compared to 14 HAIs in the non-treatment group (three CAUTIs, nine CLABSIs, and two MRSA bacteremia). Figures 1 and 2 below demonstrate HAI rates in the non-treatment and the treatment groups. Figure 1 Figure 2 Conclusion: Based on pilot results, the system approved implementation of a universal nasal antisepsis program using the 62% alcohol based nasal swab with emollients for expansion to all adult critical care units. Considerations for the future implementation of the program include broadening patient inclusion and performing ongoing HAI surveillance of treated and untreated patient groups. Disclosures: All Authors : No reported disclosures.